The role of cost saving and innovation in PFI projects (Thomas Telford, 2000)
This publication presents the findings of a study designed to test the proposition that PFI will yield value for money by stimulating innovation. It surveys people responsible for managing the purchasing, designing, building and operation of PFI projects, and poses questions about the extent to which cost saving improved value for money in various projects in both the construction and operation of facilities.
Keywords: Private Finance Initiative.; Public buildings -- Great Britain -- Finance.; Construction industry -- Great Britain -- Cost effectiveness.; Public contracts -- Great Britain.; elektronické knihy; electronic books